Evaluation of groundnut (Arachis hypogaea L.) advanced breeding lines under mid-season drought stress conditions for root traits: Evaluation of groundnut (Arachis hypogaea L.) advanced breeding lines under mid-season drought stress conditions for root traits - P LATHA; T ANITHA; A R NIRMAL KUMAR; P SUDHAKAR; R P VASANTHI; K JOHN (Journal of Oilseeds Research, 2020)
Investigation was carried out to study genotypic variability for root morphological traits among 50 advanced breeding lines of groundnut including two drought tolerant varieties (K-9 and Dharani) under both control and midseason drought stress conditions. Drought stress decreased the root length (RL), shoot length (SL), root dry weight (RDW), shoot dry weight (SDW), number of lateral roots (NLR) and root shoot ratio (RSR). Significant genotypic ranges with respect to RL, SL, RDW, SDW and NLR were 6.0-112.4, 3.9- 22.2, 0.63-2.17, 0.20-10.76 and 6.0-35.0 respectively.